If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 7)(5x + -4) = 0 Reorder the terms: (7 + 2x)(5x + -4) = 0 Reorder the terms: (7 + 2x)(-4 + 5x) = 0 Multiply (7 + 2x) * (-4 + 5x) (7(-4 + 5x) + 2x * (-4 + 5x)) = 0 ((-4 * 7 + 5x * 7) + 2x * (-4 + 5x)) = 0 ((-28 + 35x) + 2x * (-4 + 5x)) = 0 (-28 + 35x + (-4 * 2x + 5x * 2x)) = 0 (-28 + 35x + (-8x + 10x2)) = 0 Combine like terms: 35x + -8x = 27x (-28 + 27x + 10x2) = 0 Solving -28 + 27x + 10x2 = 0 Solving for variable 'x'. Factor a trinomial. (-7 + -2x)(4 + -5x) = 0Subproblem 1
Set the factor '(-7 + -2x)' equal to zero and attempt to solve: Simplifying -7 + -2x = 0 Solving -7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -2x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = 0 + 7 -2x = 0 + 7 Combine like terms: 0 + 7 = 7 -2x = 7 Divide each side by '-2'. x = -3.5 Simplifying x = -3.5Subproblem 2
Set the factor '(4 + -5x)' equal to zero and attempt to solve: Simplifying 4 + -5x = 0 Solving 4 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -5x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = 0 + -4 -5x = 0 + -4 Combine like terms: 0 + -4 = -4 -5x = -4 Divide each side by '-5'. x = 0.8 Simplifying x = 0.8Solution
x = {-3.5, 0.8}
| (x+0.9)(x+2.6)=0 | | (2n-1)/3-1/2=17/2 | | (2n-1)/3-1/5=17/5 | | 4[x+2]=18 | | X^5-x^4-1=0 | | 6(x+8)-29= | | 191+13x=360 | | 15x-12=49 | | 140/2000 | | 16x^2-24x-23=0 | | 8(x+4)-3= | | b+40+b+26=9b+5 | | -2(5x+13)-2=-6(3x-2)-41 | | 3[x-1]=49 | | 5(z+4)+1=7-(z+4) | | 12x^2-30x+48=0 | | A^2+15+54=0 | | -7=9+4c | | x-6y=50 | | t/-4-11 | | 2n/3=20/2 | | 58=4-9x | | 4s+8s= | | 5/(3x)^-4=? | | 5/(3x)^-4= | | 2Sin(X-10)=0.8 | | 2n/3=10/2 | | 5/(3x)^-4 | | 32x^2+76x-91=0 | | -4(6n-6)+4= | | .25x+.35y=5 | | x^2+4x-5=7 |